A pragmatic study of strategic maneuvering in Jane Austen’s Novels: Pride and Prejudice and Emma - Talib Salman, Hawraa (2021)
It is worth noting that language is a powerful device for writers to provoke the mind and feelings of their readers and thereby employ appropriate strategies of maneuvering to persuade them towards the writer’s perspective. It is, however, important to mention that a lot of discourse studies have been conducted on political and social genres, specifically, pragma-dialectical studies, and little researches have been done on the discourse of literary works because of its use of implicit meaning beyond the literal one and this is one the tactics of maneuvering. Thus, the current study aims to conduct a pragmatic study in an attempt to investigate the various strategies of strategic maneuvering that are available in selected novels by Jane Austen; ‘Pride and Prejudice’ and ‘Emma’. Quantitative content analysis of literary texts used an eclectic model called a pragma-dialectical analysis framework, which encompasses three stages: opening stage, argumentation stage, and concluding stage, each stage has its linguistic indicators. Analyses reveal that the speech act of question was the most prominent indicator in the opening stage of both novels. In addition, the most prominent maxim in Pride and Prejudice was the quantity maxim while Emma it was the quality maxim. Findings also revealed the scalar implicature was the most prominent implicature in both novels and as far as politeness principle is concerned, where men tend to use positive politeness more than women. The most consistent pragma-dialectical trope utilized by the writer in both novels was the rhetorical question, which is in line with Austen’s style of writing as she is known as a mistress of manipulation. Therefore, strategic maneuvering has a great reflection on Austen’s style specifically in persuading people in her thoughts and ideas. As a recommendation, the study proposes that the pragmatic structure of strategic maneuvering in both novels can best be investigated in terms of speech acts, hedges of cooperative principle, politeness principle, conversational implicatures, and pragmarhetorical tropes as shown in the conceptual framework of the study